Geoecological assessment of the dynamics of pollution of the Nura river and Samarkand reservoir - Rakhmetova, A.A.; Beisenova, R.R.; Akpambetova, K.M. (KSU Publ., 2020)
The ecological state of water bodies is formed as a result of the interaction of factors of self-purification. Anthropogenic load and is determined mainly by stationary and field studies. An actual task is to systematize theoretical and methodological approaches to the use of geo information technologies in the process of environmental research and the cartographic presentation of their results. The article discusses and analyzes the data of Kazhydromet for the period from 2008 to 2018, and assesses the quality of water by complete of hydro chemical indicators of four points. Chart diagrams were built on the analyzing data, priority substances and enterprises that make the greatest contribution to the pollution of the reservoir and river are identified.
Нұра өзені және Самарқанд су қоймасының ластану динамикасын геоэкологиялық бағалау
Геоэкологическая оценка динамики загрязнения реки Нуры и Самаркандского водохранилища
Keywords: ecological cartography; surface water quality; pollutants; hydro chemical indicators